Cure Rate of Dosimetry-based 131I Therapy in Hyperthyroidism Management - Abuqbeitah, Mohammad; Yeyin, Nami; Akyol, Sinem; Lebriz Uslu Beşli, Rabia; Demir, Mustafa (Cerrahpaşa Medical Journal, 2025)
Background: This study aims to evaluate the effectiveness and cure rate of individualized radioiodine therapy in patients diagnosed with Graves’ disease and toxic adenoma. Methods: A total of 11 patients with toxic adenoma and 20 patients with Graves’ disease were enrolled in the study. Radioiodine activities were individually calculated using patient-specific data and a mathematical model to deliver target absorbed doses of 300 Gy for toxic adenoma and 200 Gy for Graves’ disease. The mean administered radioactive iodine (RAI) activity was 826 ± 124 MBq for patients with toxic adenoma and 541 ± 215 MBq for those with Graves’ disease. Results: At the 3-month follow-up, 35% of patients with Graves’ disease and 54.6% of those with toxic adenoma reached a euthyroid state. Hypothyroidism occurred in 65% of Graves’ patients and 45.4% of toxic adenoma patients; all began thyroid hormone replacement therapy and achieved euthyroid status by the 6-month follow-up. Conclusion: Dosimetry-based RAI therapy achieved complete remission within 3 months following a single administration of 131I, with no patients requiring a second course of RAI therapy. In contrast to empirical treatment protocols, individualized therapy enhances safety, minimizes risk, and improves clinical outcomes. Cite this article as: Abuqbeitah M, Yeyin N, Akyol S, Uslu-Beşli L, Demir M. Cure rate of dosimetry-based 131I therapy in hyperthyroidism management. Cerrahpaşa Med J 2025, 49, 0032, doi: 10.5152/cjm.2025.25032.